Outcome of pregnancy in IVF-ET cycle at Ramathibodi Hospital. - C. Srisombut (2018)
As assisted reproductive technology is being developed, in vitro fertilization and embryo transfer (IVF-ET) are the treatments of choice for many infertility problems. The outcome of pregnancies achieved by IVF-ET is different from that of spontaneous pregnancies. In this retrospective study, the outcome of pregnancies from 400 IVF treatment cycles performed from October 1991 to October 1994 were reported. There were 80 pregnancies (20% per oocyte retrieval, 21.9% per embryo transfer) with an increased rate of abortion (30%), multiple pregnancy (20%), ectopic pregnancy (6.25%), heterotopic pregnancy (1.25%), preterm delivery (11.8%), low birth weight (35.8%) and cesarean section (62.7%). This study shows that the complication rate of pregnancies from IVF-ET cycles was higher than that found in spontaneous pregnancies. Some complications such as multiple pregnancies may be prevented by limiting the number of transferred embryos. From this study, all IVF-ET pregnancy should be considered as high risk pregnancies.